Correlation between Handgrip Strength and Pulmonary Function Parameters (% Predicted) in an Urban Adult Population - Yohanes Firmansyah; Ajeng Tias Endarti; Nur Asniati Djaali; Ernawati Ernawati (Universitas Malahayati, 2026)
ABSTRACT Handgrip strength is a simple indicator of peripheral muscle strength that may reflect pulmonary function status, particularly in urban adult populations exposed to high levels of air pollution. However, empirical evidence regarding the association between handgrip strength and predicted pulmonary function parameters in Indonesia remains limited. This study aimed to analyze the correlation between handgrip strength and pulmonary function parameters (% predicted) in an urban adult population. An observational analytic study with a cross-sectional design was conducted among 539 adults (≥18 years) across five administrative regions of DKI Jakarta. Pulmonary function parameters assessed included vital capacity (VC), forced vital capacity (FVC), forced expiratory volume in one second (FEV₁), and the FEV₁/FVC ratio, all expressed as % predicted. Handgrip strength was measured bilaterally and averaged. Univariate and bivariate analyses were performed using Spearman’s correlation test. Mean handgrip strength showed a significant positive correlation with VC (% predicted) (r = 0.182; p 0.001) and FVC (% predicted) (r = 0.222; p 0.001). A weaker positive correlation was observed between left-hand grip strength and FEV₁ (% predicted) (r = 0.091; p = 0.034). In contrast, the FEV₁/FVC ratio (% predicted) demonstrated consistent and significant negative correlations with right-hand, left-hand, and mean handgrip strength (r ranging from −0.186 to −0.200; p 0.001). Handgrip strength is significantly associated with pulmonary function capacity (% predicted), particularly volume-related parameters, and may serve as a simple screening indicator of pulmonary function in urban adult populations. Keywords: Handgrip, Pulmonary Function, Spirometry, Adults, Urban Population.